Ivor Horton's beginning Visual C++ 2012 - Horton, Ivor. (Hoboken, N.J. : Wiley ; Chichester : John Wiley [distributor], 2012)
The only book to teach C++ programming with Microsoft Visual Studio! There's a reason why Ivor Horton's Beginning Visual C++ books dominate the marketplace. Ivor Horton has a loyal following who love his winning approach to teaching programming languages, and in this fully updated new edition, he repeats his successful formula. Offering a comprehensive introduction to both the standard C++ language and to Visual C++, he offers step-by-step programming exercises, examples, and solutions to deftly guide novice programmers through the ins and outs of C++ development. Introduces novice programmers.
Print version record.
Keywords: Microsoft Visual C++.; C++ (Computer program language; C++ (Computer program language); Electronic books